2014
DOI: 10.1002/jor.22650
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells reduce pain but not degenerative changes in a mono-iodoacetate rat model of osteoarthritis

Abstract: ABSTRACT:We studied the effects of intra-articularly injected bone marrow derived mesenchymal stem cells (MSCs), as well as freshly isolated bone marrow mononuclear cells (BMMNCs), on pain, cartilage damage, bone changes and inflammation in an in-vivo rat osteoarthritis (OA) model. OA was induced unilaterally by injection of mono-iodoacetate (MIA) and allowed to develop for 3 weeks. Then, animals were treated by intra-articular injection with MSCs, BMMNCs, or saline as a control. Four weeks later, pain was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 42 publications
5
69
2
Order By: Relevance
“…Although the exact mechanism of action of MSCs on pain reduction is not known, anti-inflammatory activity has been attributed to this effect. To date, some studies have demonstrated the role of MSCs on OA-induced pain behavior [35–37]. Van Buul et al reported improvement of weight-bearing joints of the affected limb after intra-articular application of both rat and human BMMSCs in MIA-induced OA rats [37].…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of action of MSCs on pain reduction is not known, anti-inflammatory activity has been attributed to this effect. To date, some studies have demonstrated the role of MSCs on OA-induced pain behavior [35–37]. Van Buul et al reported improvement of weight-bearing joints of the affected limb after intra-articular application of both rat and human BMMSCs in MIA-induced OA rats [37].…”
Section: Discussionmentioning
confidence: 99%
“…Poor graft survival has now been generally accepted as a major hurdle for successful cell therapy in regenerative medicine approaches, therefore much effort is currently put into strategies to improve graft survival. [137][138][139][140][141] Clearly, in vivo cell tracking can provide valuable information for the design and use of cell-based treatment strategies. Unfortunately, current limitations imposed by practical, technical and regulatory issues still prevent widespread clinical use of available imaging technology.…”
Section: Clinically Relevant Insights Gained From Pre-clinical Studiementioning
confidence: 99%
“…In addition to the extra regulatory and patient burden, once the cells are implanted, they die at an accelerated rate, typically with only a few percentage of the implanted cells found to survive more than a few weeks in the body. 41, 44, 55 This may be due to a relatively rapid change in environment for these cells, from the carefully monitored and controlled in vitro environment to an in vivo environment which may have significantly less nutrition or oxygen.…”
Section: Section One: a Review Of The Science Behind Bio-enhanced Aclmentioning
confidence: 99%